New distributional records of Cleome chelidonii L.f. and Cleome rutidosperma DC. (Cleomaceae) in Madura Island - Arifin Surya Dwipa Irsyam; Muhammad Rifqi Hariri; Ashari Bagus Setiawan; Rina Ratnasih Irwanto; Asih Perwita Dewi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Calcareous soil and dry climate are characteristic of Madura Island, located on the east coast of Java, Indonesia. The group of flowering plants that adapted to these conditions is the genus Cleome L. (Cleomaceae). In 1963, Backer and Bakhuizen van den Brink Jr. only listed three species of Cleome from Madura, i.e., C. aspera J.König ex DC., C. gynandra L., and C. viscosa L. Since then, the updated data on the genus Cleome of Madura is not provided yet. Therefore, this study aimed to provide updated information on the genus in Madura island. The botanical exploration was conducted at Bangkalan, Sampang, Pamekasan, and Sumenep in December 2019 to January 2020. The two additional species, namely C. chelidonii L.f. and C. rutidosperma DC., were reported for the first time in Madura. Both species were considered as the newly distributional record for the island. Cleome chelidonii was found in Gapura Tengah (Sumenep Regency), and C. rutidosperma was collected from Kamal (Bangkalan Regency). The botanical information on both species is presented, including the updated key to the Cleome of Madura Island. This study provides updated information on genus Cleome in Madura and reporting the existence of Cleome chelidonii and Clome rutidosperma from the island. The presence of both species was considered as a newly distributional record.